PENGARUH KOMPLEKSITAS PERUSAHAAN, REPUTASI KAP, DAN LEVERAGE TERHADAP AUDIT FEE PADA SEKTOR INDUSTRI BARANG CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 - 2022 - Dania, Saraswati; Lodang Prananta Widya, Sasana (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2024)
This research aims to test and obtain empirical evidence regarding the influence of company complexity, reputation KAPand Leverage on audit Fees. This research uses a sample of goods and consumer sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling method used in this research is the purposive sampling method using Eviews 9 for data analysis. This type of research is quantitative with 23 companies used as research samples with observations for 6 years, so the total research sample is 115 samples. The analysis technique used is panel data regression. The results of this research show that simultaneously, company complexity, reputation KAP and Leverage have an effect on audit Fees, partially, company complexity has an effect on audit Fees, partially, reputation KAPhas no effect on audit Fees, partially, Leverage has no effect on audit Fees.